Venture Capital and the Financing of Innovation - Guilhon, Bernard; Montchaud, Sandra (Innovation, entrepreneurship and management series. Innovation between risk and reward set, 2020)
The funding of innovative projects that are fundamentally ambiguous often leads to situations where decision-making is difficult. However, decision-making can be improved by practices such as syndication and step-by-step funding. The dynamic of this industry requires us to consider the economic and institutional variables that make this system coherent in English-speaking countries, but conversely reduce it to a privileged niche by the leading authorities in Europe and France. This book proposes two guiding ideas. The first idea presents innovation as a very uncertain process. This modifies the decision-making in the entrepreneurial ecosystem, with intervention upstream in regards to stronger foundations, evaluations and selection of projects. The second idea is that the actors hold onto partial knowledge in a context where their attention span is limited. These cognitive limitations need the formation of networks, and lead to mutual and complementary dependency relations.